2022
DOI: 10.1038/s41598-022-23656-1
|View full text |Cite
|
Sign up to set email alerts
|

Graph-generative neural network for EEG-based epileptic seizure detection via discovery of dynamic brain functional connectivity

Abstract: Dynamic complexity in brain functional connectivity has hindered the effective use of signal processing or machine learning methods to diagnose neurological disorders such as epilepsy. This paper proposed a new graph-generative neural network (GGN) model for the dynamic discovery of brain functional connectivity via deep analysis of scalp electroencephalogram (EEG) signals recorded from various regions of a patient’s scalp. Brain functional connectivity graphs are generated for the extraction of spatial–tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…As mentioned in the earlier section, the forward and backward propagation all together contribute to this efficiency. [32][33][34] The difference in terms of rate of accuracy is significantly observable, which in all cases of the specimens is more than 2%. Finally, in Table 3, comparison of the performance designed work is made with respect to three other competent schemes.…”
Section: Experimental Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…As mentioned in the earlier section, the forward and backward propagation all together contribute to this efficiency. [32][33][34] The difference in terms of rate of accuracy is significantly observable, which in all cases of the specimens is more than 2%. Finally, in Table 3, comparison of the performance designed work is made with respect to three other competent schemes.…”
Section: Experimental Analysismentioning
confidence: 90%
“…Deep graph neural networks (GNNs) for seizure prediction from MRI data is introduced. 32 They model brain connectivity using GNNs to enhance prediction accuracy. The study reported a prediction accuracy of 94%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adversaries possess the capability to launch attacks on the autopilot system of autonomous vehicles by attaching stickers to traffic signs. The fact that most patch attack methods do not consider the issue of determining the ideal spot in an image to inject the patch is a significant restriction [115]. Current patch attack methods either learn patches that are universal across locations or use a fixed place as the patch site.…”
Section: A Patch Attacksmentioning
confidence: 99%
“…Most epilepsy diagnosis studies use EEG data. Li et al [158] proposed a structuregenerated GNN model for learning the spatial-temporal dynamic features of EEG signals. Tao et al [101] constructed dynamic brain networks from EEG and used a GIN model to predict seizure.…”
Section: Epilepsymentioning
confidence: 99%